2018
DOI: 10.1089/lap.2017.0560
|View full text |Cite
|
Sign up to set email alerts
|

Polytetrafluoroethylene-Covered Stent Graft Versus Bare Stent in Transjugular Intrahepatic Portosystemic Shunt: Systematic Review and Meta-Analysis

Abstract: CS is associated with better primary patency and survival and lesser rate of rebleeding than BS in patients undergoing TIPS procedure. There is no difference in new-onset hepatic encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…HE is the most common complication, but stent type and operators' skills also affect the outcomes of TIPS [21]. Rebleeding mostly occurs because of the stent stenosis and occlusion [7]. Thus, a commonly used therapy for such cases is TIPS revision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HE is the most common complication, but stent type and operators' skills also affect the outcomes of TIPS [21]. Rebleeding mostly occurs because of the stent stenosis and occlusion [7]. Thus, a commonly used therapy for such cases is TIPS revision.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, covered stent graft such as polytetrafluoroethylene-(PTFE-) covered stent has been developed to improve the stent patency. Triantafyllou et al concluded that the 1-year primary patency of stent rose from 52% to 84% by using covered stent instead of the bare stent, while rebleeding rate dropped from 18% to 9% [7]. In clinical practice, patients at high risk, NSBB nonresponder, and patients with extraluminal collaterals prefer to receive TIPS treatment first since it has been established that endoscopic treatments are less effective in these patients [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Remarks Covered stents are less prone to occlusion as the PTFE covering prevents pseudo intimal hyperplasia and acute thrombosis which is mostly related to bile intravasation into the stent. 122,123 Studies have shown covered stents to have a better patency and survival rates in patients with variceal bleeding and ascites. [124][125][126] Q11.…”
Section: Remarksmentioning
confidence: 99%
“…57 A recent meta-analysis comparing covered stents and metallic stents analyzed 14 studies (4 randomized clinical trials, 2 prospective nonrandomized studies, and 8 retrospective studies; 2,519 patients total) and demonstrated that odds of patency (odds ratio, OR ¼ 4.75) and survival (OR ¼ 1.85) were significantly higher for PTFE-covered stent grafts, while odds of rebleeding were significantly lower (OR ¼ 0.37). 84 Thus, the role of embolotherapy remains uncertain in our current era and questions about its use have been raised given involved cost, radiation exposure, procedure duration, and risk of postembolization syndrome. 72,85 TIPS in VH, Rescue, and Emerging Early TIPS TIPS is highly effective for rescue therapy for both EVH and GVH.…”
Section: Embolotherapy and Tipsmentioning
confidence: 99%